Sodium niobate-based energy storage ceramic material and its preparation method and application
By introducing linear dielectric Bi0.1Sr0.85TiO3 and a relaxant doped with BiMg2/3Nb1/3O3 in NaNbO3, the problem of reducing the energy storage density of sodium niobate-based ceramic materials under the midfield strength is solved, and ceramic materials with high energy storage density under the midfield strength are realized, avoiding safety hazards under the high field strength.
Patent Information
- Application Number
- CN202410794453.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-19
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-06-19
AI Technical Summary
Existing sodium niobate-based ceramic materials can only obtain high energy storage density under high field strength, resulting in a decrease in energy storage density under midfield strength, and there are safety hazards and equipment loss problems under high operating voltage.
By introducing linear dielectric Bi0.1Sr0.85TiO3 into NaNbO3 to form a solid solution and doping BiMg2/3Nb1/3O3, the doping amount of the relaxant is controlled at 0
It achieves high energy storage density under midfield strength, avoids safety hazards and equipment losses under high field strength, and improves the relaxation and energy storage efficiency of ceramics.
Smart Images

Figure CN118834066B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage ceramic materials, and in particular to a sodium niobate-based energy storage ceramic material and a preparation method and application thereof. Background Art
[0002] Faced with the problems caused by the depletion of fossil energy and environmental pollution, the development of clean energy and sustainable renewable energy has become increasingly urgent. Therefore, the research and development of clean energy storage devices is also particularly important.
[0003] In clean energy storage devices, dielectric ceramic capacitors have broad application prospects in clean energy storage devices due to their ultra-high power density, ultra-fast charge and discharge rate, wide operating temperature range, and excellent working stability.
[0004] Dielectric ceramic materials have become the core component of dielectric ceramic capacitors because of their influence on the dielectric constant, dielectric loss, breakdown strength, temperature stability, mechanical strength, chemical stability, and environmental adaptability of dielectric ceramic capacitors.
[0005] At present, dielectric ceramic materials mainly include perovskite structural materials such as bismuth ferrite-based, barium titanate-based, strontium titanate-based, sodium bismuth titanate-based, silver niobate-based, sodium niobate-based, etc. Among them, sodium niobate (NaNbO3) is a material with high application potential due to its good antiferroelectric properties and high saturation polarization strength.
[0006] When sodium niobate is used in dielectric ceramic materials, it is usually doped with elements at the A or B position of the perovskite structure of NaNbO3 to enhance the relaxation characteristics, optimize the energy storage characteristics such as improving the breakdown field strength and reducing the residual polarization, and obtain higher energy storage density and efficiency. For example, the patent application with application number 202311619513.6, entitled "A lanthanum-doped high energy storage sodium niobate-based ceramic and its preparation method and application", discloses that by doping La in NaNbO3 3+ And a higher energy storage density (>4J / m 3 )’s technical solution.
[0007] However, this kind of NaNbO3-based ceramic with high energy storage density needs to be obtained under a higher field strength (>400kV / cm), and high field strength is accompanied by a high operating voltage. When this energy storage device operates for a long time under a high operating voltage, it may cause safety problems due to heat or cause large losses in the device; moreover, high field strength will also limit the conditions of the equipment's long-term operating environment. This not only limits the development of NaNbO3-based ceramic materials, but also limits the application of NaNbO3-based ceramic materials in wearable devices and microelectronic devices. If NaNbO3-based ceramics can be used under medium and long strengths, these safety issues can be avoided. Therefore, the research and development of NaNbO3-based ceramics that can obtain high energy storage density under medium and medium strengths is particularly important for the development of dielectric ceramics. Summary of the invention
[0008] In order to solve at least one of the above problems, the inventors have repeatedly studied NaNbO3-based ceramic materials and found that NaNbO3-based ceramic materials with high energy storage density can be achieved by increasing the breakdown field strength of the ceramic, maintaining the saturation polarization and reducing the residual polarization. However, the reason why NaNbO3-based ceramics with high energy storage density can only be obtained under high field strength is that when improving the energy storage density of NaNbO3-based ceramics, the breakdown field strength of the ceramics is often increased only by doping, while the decrease in saturation polarization value is ignored. In order to solve this problem, the inventors thought of increasing the breakdown field strength of NaNbO3-based ceramics by doping Bi 3+ To maintain the high saturation polarization of the ceramic as much as possible, but Bi 3+ Too high a doping amount of Bi2O3 will lead to the appearance of Bi2O3 impurity phase, which will cause the breakdown field strength to decrease and the residual polarization to be larger; while Bi 3+ If the doping amount is too low, the saturation polarization will decrease. That is, the energy storage density of the ceramic will be affected if the doping amount is too high or too low. How to balance the breakdown field strength, saturation polarization and residual polarization of NaNbO3-based ceramics is a difficult problem in obtaining NaNbO3-based high energy storage density ceramics under medium field strength.
[0009] The inventors conducted further research on the breakdown field strength, saturation polarization and remanent polarization of balanced NaNbO3-based ceramics and found that by dissolving Bi in NaNbO3 3+ Linear dielectric, then doped with Bi-rich 3+ By adding a relaxant to improve the relaxation characteristics of the ceramic and controlling the doping amount of the relaxant, the obtained NaNbO3-based ceramic can maintain a high polarization characteristic while improving the breakdown field strength, so that the obtained NaNbO3-based ceramic still has a high energy storage density under medium field strength. Therefore, according to one aspect of the present invention, a sodium niobate-based energy storage ceramic material is provided.
[0010] The general formula of the sodium niobate-based energy storage ceramic material is: (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM; A 0.1 D 0.85 EG3 is a general formula of a linear dielectric dissolved in NaNbO3; AM is a relaxation agent capable of improving the relaxation characteristics of sodium niobate-based energy storage ceramic materials; wherein A is a Bi element; and the value range of x is 0<x≤0.16.
[0011] Since the sodium niobate-based energy storage ceramic material of the present invention firstly solid-dissolves Bi in NaNbO3 3+ The general formula is A 0.1 D 0.85 The linear dielectric of EG3 has the general formula 0.85NaNbO3-0.15A 0.1 D 0.85 EG3 solid solution; then in the general formula 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with Bi-rich 3+ A relaxation agent capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material of the present invention, the general formula of the relaxation agent is AM, wherein A is a Bi element, and the amount of the doped relaxation agent is controlled to be 0<x≤0.16, so that the obtained NaNbO3-based ceramic can maintain a relatively high polarization characteristic while improving the breakdown field strength (this is because compared with the ferroelectric materials and antiferroelectric materials commonly used in energy storage ceramic materials, linear dielectrics have a relatively high breakdown electric field, therefore, first doping linear dielectrics in NaNbO3 can preliminarily improve the breakdown electric field strength of the energy storage ceramic material; at the same time, since the selected linear dielectric contains Bi ions, it is beneficial for NaNbO3 to maintain a relatively high polarization value after solid dissolving the linear dielectric containing Bi ions), thereby achieving high energy storage density under medium field strength.
[0012] In some embodiments, D is an Sr element; and / or E is a Ti element; and / or G is an O element.
[0013] In some embodiments, the relaxant is a relaxor ferroelectric.
[0014] In some embodiments, M is of the general formula H 2 / 3 J 1 / 3 G3 or general formula H 0.5 L 0.5 G3.
[0015] In some embodiments, H is Mg element; and / or J is Nb element; and / or G is O element; and / or L is Hf element or Zr element.
[0016] In some embodiments, the value of x is 0.04, 0.08, 0.12 or 0.16. Preferably, the value of x is 0.08. This is because the ceramic material obtained with a lower doping amount has a lower relaxivity and cannot achieve the effect of improving the breakdown field strength; a higher doping amount will cause the ceramic to reach the solid solubility limit, produce defects such as impurities or oxygen vacancies, and lead to performance degradation. At the same time, the saturation polarization intensity will also decrease with the increase of the doping amount. These factors together lead to a decrease in energy storage density.
[0017] The present invention introduces a linear dielectric Bi into NaNbO3 0.1 Sr 0.85 TiO3 forms 0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3 solid solution, doped with a certain amount of relaxation agent BiMg 2 / 3 Nb 1 / 3 O3 to obtain (1-x)(0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3)-xBiMg 2 / 3 Nb 1 / 3 O3 ceramic material, wherein the value range of x is 0<x≤0.16.
[0018] Introduction of linear dielectric Bi into NaNbO3 0.1 Sr 0.85 TiO3 forms 0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3 solid solution has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density.
[0019] BiMg 2 / 3 Nb 1 / 3 The introduction of O3 not only disrupts the long-range ordered ferroelectric domains, forming polar nano-regions inside NaNbO3-based ceramics, reducing the residual polarization, but also improves the breakdown field strength of NaNbO3-based ceramics; in addition, Bi 0.1 Sr 0.85 TiO3 and BiMg 2 / 3 Nb 1 / 3 The introduction of O3 increases the Bi content of NaNbO3-based ceramics. 3+ The content maintains the high saturation polarization of the ceramics, so that the NaNbO3-based ceramics can still obtain a higher energy storage density under medium field strength.
[0020] This patent introduces Bi into NaNbO3 0.1 Sr 0.85 TiO3 and BiMg 2 / 3 Nb 1 / 3O3 increases the disorder of the A-site and B-site ions of the perovskite structure, resulting in lattice distortion and twisting. The long-range ferroelectric domains of NaNbO3 are disturbed and converted into polar nano-regions, which enhances the relaxivity of the ceramics, helps to reduce the residual polarization strength of the ceramics, and also helps to increase the breakdown electric field strength of the ceramics. In addition, due to (1-x)(0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3)-xBiMg 2 / 3 Nb 1 / 3 O3 ceramics are rich in Bi 3+ ions, the hybridization of Bi's 6s orbital and O's 2p orbital enables the ceramic material to maintain a higher maximum polarization value.
[0021] When the doped relaxation agent is Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5 )O3, although due to its Nb 5+ The content is less than BiMg 2 / 3 Nb 1 / 3 Nb in O3 5+ The content of 2 / 3 Nb 1 / 3 O3 is slightly weaker than that of BiMg, which will result in the breakdown field strength and saturation polarization value being similar to that of 2 / 3 Nb 1 / 3 O3 is slightly lower than that of the conventional NaNbO3-based ceramics, which leads to a slightly lower energy storage density. However, compared with the NaNbO3-based ceramics in the prior art, Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5 )O3 high concentration Bi 3+ It is still beneficial to maintain a high saturation polarization; and Mg 2+ and Hf 4+ The introduction of can still refine the grains and destroy the long-range ferroelectric order of NaNbO3-based ceramics, and can induce the formation of polar nano-regions with excellent relaxation properties, thereby achieving the effect of reducing the residual polarization intensity.
[0022] Bi-rich 3+ BiMg 2 / 3 Nb 1 / 3 O3、Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5 )O3 as a relaxation agent, so that the A site in the obtained NaNbO3-based perovskite ceramic structure has a high concentration of Bi 3+, which is conducive to maintaining a higher saturation polarization, thereby obtaining a high energy storage density under medium field strength.
[0023] According to one aspect of the present invention, a method for preparing a sodium niobate-based energy storage ceramic material is provided, which comprises the following steps:
[0024] S10: NaNbO3 is used as the first matrix, and the solid solution formula in the first matrix is A 0.1 D 0.85 EG3 is a linear dielectric, and the general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 Solid solution of EG3;
[0025] S20: The general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with a relaxant capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material, wherein the general formula of the relaxant is AM, and the general formula is (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM sodium niobate-based energy storage ceramic materials;
[0026] Wherein, A is Bi element;
[0027] The value range of x is 0<x≤0.16.
[0028] Since the sodium niobate-based energy storage ceramic material of the present invention firstly solid-dissolves Bi in NaNbO3 3+ The general formula is A 0.1 D 0.85 The linear dielectric of EG3 has the general formula 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density; in the general formula of 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with Bi-rich 3+ A relaxation agent capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material of the present invention, the general formula of the relaxation agent is AM, wherein A is a Bi element, and the amount of the doped relaxation agent is controlled within the range of 0 to 0.16, so that the obtained NaNbO3-based ceramic can maintain a relatively high polarization characteristic while improving the breakdown field strength, thereby achieving a high energy storage density under a medium field strength.
[0029] According to another aspect of the present invention, a method for preparing a sodium niobate-based energy storage ceramic material is provided, which comprises the following steps:
[0030] S100: According to the general formula (1-x) (0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM weigh the raw materials, M is the general formula H 2 / 3J 1 / 3 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, or M is a general formula H 0.5 L 0.5 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, LG2;
[0031] S200: preparing the raw material into powder;
[0032] S300: granulating the prepared powder;
[0033] S400: forming and tableting the granulated raw materials to form a ceramic embryo;
[0034] S500: Sintering the ceramic body to obtain a general formula of (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramics; wherein A is Bi element; and the value range of x is 0<x≤0.16.
[0035] The method of the present invention is not only simple in process for preparing sodium niobate-based energy storage ceramic materials, but also can ensure that the prepared sodium niobate-based energy storage ceramic materials have the characteristics of good uniformity and high stability, and lead pollution can be avoided during the preparation process.
[0036] In some embodiments, D is Sr element; and / or E is Ti element; and / or G is O element; and / or H is Mg element; and / or J is Nb element; and / or L is Hf element or Zr element.
[0037] Introduction of linear dielectric Bi into NaNbO3 0.1 Sr 0.85 TiO3 forms 0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3 solid solution has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density. 3+ BiMg 2 / 3 Nb 1 / 3 O3、Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5)O3 as a relaxation agent, so that the A site in the obtained NaNbO3-based perovskite ceramic structure has a high concentration of Bi 3+ , which is conducive to maintaining a higher saturation polarization, thereby obtaining a high energy storage density under medium field strength.
[0038] In some embodiments, in step S500, during the sintering process, the temperature is increased from 350°C to 500°C at a heating rate of 5°C / min, and is kept at 500°C for 2 hours; and / or the temperature is increased from room temperature to 1150-1200°C at a heating rate of 5-8°C / min, and is kept at 1200°C for 3-5 hours.
[0039] Since Na ions and Bi ions are easily volatilized at high temperatures, some oxygen vacancies will be generated, causing defects in the ceramic. The present invention greatly reduces the volatilization problem of Na ions and Bi ions, reduces the defects of the ceramic, and ensures the energy storage performance of the ceramic by controlling the sintering temperature, heating rate and holding time.
[0040] According to one aspect of the present invention, there is provided an application of a sodium niobate-based energy storage ceramic material in a device operating under a medium-field strength. The sodium niobate-based energy storage ceramic material is the aforementioned sodium niobate-based energy storage ceramic material, or is a sodium niobate-based energy storage ceramic material prepared by the aforementioned method for preparing a sodium niobate-based energy storage ceramic material. For example, the ceramic prepared from the ceramic material of the present invention is used as a dielectric between the positive and negative electrodes of the capacitors of these devices. These devices are, for example, wearable devices or microelectronic devices. Since the greater the electric field strength received by the capacitors in some wearable devices and microelectronic devices, the easier it is to be broken down, and the greater the potential safety hazard, therefore, the ceramic material obtained by the present invention that still has a high energy storage density under a medium-field strength is more suitable for use in wearable devices and microelectronic devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 A schematic flow chart of a method for preparing a sodium niobate-based energy storage ceramic material according to an embodiment of the present invention;
[0042] Figure 2 A schematic flow chart of a method for preparing a sodium niobate-based energy storage ceramic material according to another embodiment of the present invention;
[0043] Figure 3 is an X-ray diffraction pattern of a sodium niobate-based ceramic material with a doping amount of x=0.00 to 0.16;
[0044] Figure 4 It is the unipolar hysteresis loop diagram of sodium niobate-based ceramic material with doping amount x=0.00;
[0045] Figure 5 It is the unipolar hysteresis loop diagram of sodium niobate-based ceramic material with doping amount x=0.04;
[0046] Figure 6 It is the unipolar hysteresis loop diagram of sodium niobate-based ceramic material with doping amount x=0.08;
[0047] Figure 7 It is the unipolar hysteresis loop diagram of sodium niobate-based ceramic material with doping amount x=0.12;
[0048] Figure 8 It is the unipolar hysteresis loop diagram of sodium niobate-based ceramic material with doping amount x=0.16;
[0049] Fig. 9 This is a graph showing the changes in energy storage density and energy storage efficiency of sodium niobate-based ceramic materials with doping amounts x=0.00 to 0.16. DETAILED DESCRIPTION
[0050] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.
[0051] It should also be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. Moreover, the terms "include" and "comprise" include not only those elements, but also other elements that are not explicitly listed, or also include elements inherent to such processes, methods, articles or equipment. In the absence of further restrictions, the elements defined by the statement "include..." do not exclude the existence of other identical elements in the process, method, article or equipment that includes the elements. The terms used in this article are generally commonly used terms by those skilled in the art. If they are inconsistent with commonly used terms, the terms in this article shall prevail.
[0052] In this article, the term "linear dielectric" refers to a dielectric material whose polarization intensity varies linearly with the electric field strength within a certain range of electric field strength, so that the dielectric constant does not change with the electric field.
[0053] In this article, the term "relaxation" refers to the process in which a macroscopic equilibrium system becomes a non-equilibrium state due to changes in the surrounding environment or external influences, and the system then transitions from the non-equilibrium state to a new equilibrium state.
[0054] In this article, the term "ferroelectric" refers to a crystal that has spontaneous polarization within a certain temperature range and whose spontaneous polarization direction can be reversed by reversing the direction of an external electric field.
[0055] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] According to one embodiment of the present invention, a sodium niobate-based energy storage ceramic material is provided.
[0057] The general formula of the sodium niobate-based energy storage ceramic material is: (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM; A 0.1 D 0.85 EG3 is a general formula of a linear dielectric dissolved in NaNbO3; AM is a relaxation agent capable of improving the relaxation characteristics of sodium niobate-based energy storage ceramic materials; wherein A is a Bi element; and the value range of x is 0 to 0.16.
[0058] Since the sodium niobate-based energy storage ceramic material of the present invention firstly solid-dissolves Bi in NaNbO3 3+ The general formula is A 0.1 D 0.85 The linear dielectric of EG3 is obtained with a high saturation polarization value and the general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is conducive to obtaining a higher energy storage density; then in the general formula of 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with Bi-rich 3+ A relaxation agent capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material of the present invention, the general formula of the relaxation agent is AM, wherein A is a Bi element, and by controlling the amount of the doped relaxation agent to be 0<x≤0.16, the obtained NaNbO3-based ceramic can maintain a relatively high polarization characteristic while improving the breakdown field strength, thereby achieving a high energy storage density under a medium field strength.
[0059] In some embodiments, D is Sr; and / or E is Ti; and / or G is O, that is, the linear dielectric is Bi. 0.1 Sr 0.85 TiO3. Introducing linear dielectric Bi into NaNbO3 0.1 Sr 0.85 TiO3 forms 0.85NaNbO3-0.15Bi 0.1 Sr 0.85TiO3 solid solution has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density.
[0060] In some embodiments, the relaxor is a relaxor ferroelectric. In some embodiments, in the relaxor of formula AM, M is a relaxor of formula H 2 / 3 J 1 / 3 G3 or general formula H 0.5 L 0.5 G3. In some specific embodiments, H is Mg; and / or J is Nb; and / or G is O; and / or L is Hf or Zr. 2 / 3 Nb 1 / 3 O3、Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5 )O3 is a relaxation agent, and the A position in the obtained NaNbO3-based perovskite ceramic structure has a high concentration of Bi 3+ , which is conducive to maintaining a higher saturation polarization, thereby obtaining a high energy storage density under medium field strength.
[0061] In some embodiments, the value of x is 0.04, 0.08, 0.12 or 0.16.
[0062] The present invention introduces Bi-rich 3+ , the general formula is A 0.1 D 0.85 EG3's linear dielectric has the general formula 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with a certain amount of Bi-rich 3+ The relaxation agent of the general formula AM is obtained as follows: (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramic material, wherein A is Bi element and the value range of x is 0<x≤0.16.
[0063] Existing sodium niobate-based ceramic materials often require a larger electric field strength to obtain a larger energy storage density. The introduction of Bi-rich 3+ , the general formula is A 0.1 D 0.85 The linear dielectric formula of EG3 is 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density; doping a certain amount of Bi-rich 3+The relaxation agent of the general formula AM is obtained as follows: (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramic material (i.e., NaNbO3-based perovskite ceramic structure), because the A position in the obtained NaNbO3-based perovskite ceramic structure has a high concentration of Bi 3+ , which is conducive to maintaining a higher saturation polarization, thereby obtaining a high energy storage density under medium field strength.
[0064] Figure 1 The preparation method of the sodium niobate-based energy storage ceramic material according to one embodiment of the present invention is shown as an example. Figure 1 As shown, the preparation method of the sodium niobate-based energy storage ceramic material comprises the following steps:
[0065] S10: NaNbO3 is used as the first matrix, and the solid solution formula in the first matrix is A 0.1 D 0.85 EG3 is a linear dielectric, and the general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 Solid solution of EG3;
[0066] S20: The general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with a relaxant capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material, wherein the general formula of the relaxant is AM, and the general formula is (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM sodium niobate-based energy storage ceramic materials;
[0067] Wherein, A is Bi element;
[0068] The value range of x is 0<x≤0.16.
[0069] Since the sodium niobate-based energy storage ceramic material of the present invention firstly solid-dissolves Bi in NaNbO3 3+ The general formula is A 0.1 D 0.85 The linear dielectric of EG3 has the general formula 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density; in the general formula of 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with Bi-rich 3+A relaxation agent capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material of the present invention, the general formula of the relaxation agent is AM, wherein A is a Bi element, and the amount of the doped relaxation agent is controlled within the range of 0 to 0.16, so that the obtained NaNbO3-based ceramic can maintain a relatively high polarization characteristic while improving the breakdown field strength, thereby achieving a high energy storage density under a medium field strength.
[0070] Figure 2 The preparation method of sodium niobate-based energy storage ceramic material according to another embodiment of the present invention is shown as an example. Figure 2 As shown, the preparation method of the sodium niobate-based energy storage ceramic material comprises the following steps:
[0071] S100: According to the general formula (1-x) (0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM weigh the raw materials, M is the general formula H 2 / 3J 1 / 3 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, or M is a general formula H 0.5 L 0.5 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, LG2;
[0072] S200: preparing the raw material into powder;
[0073] S300: granulating the prepared powder;
[0074] S400: forming and tableting the granulated raw materials to form a ceramic embryo;
[0075] S500: Sintering the ceramic body to obtain a general formula of (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramics; wherein A is Bi element; and the value range of x is 0<x≤0.16.
[0076] The present invention is to dissolve A in NaNbO3 0.1 D 0.85 EG3, doped with A 0.1 D 0.85 EG3 optimizes the energy storage performance of ceramics through linear dielectrics, and further improves the breakdown electric field strength of ceramics through doped relaxation agents, reduces the residual polarization value of ceramics, and thus improves the energy storage performance. The method of the present invention is not only simple to prepare sodium niobate-based energy storage ceramic materials, but also can ensure that the prepared sodium niobate-based energy storage ceramic materials have the characteristics of good uniformity and high stability, and lead pollution can be avoided during the preparation process.
[0077] In some embodiments, D is Sr; and / or E is Ti; and / or G is O; and / or H is Mg; and / or J is Nb; and / or L is Hf or Zr. 0.1 Sr 0.85 TiO3 forms 0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3 solid solution has a higher saturation polarization value, which is conducive to obtaining a higher energy storage density. 3+ BiMg 2 / 3 Nb 1 / 3 O3、Bi(Mg 0.5 Hf 0.5 )O3 or Bi(Mg 0.5 Zr 0.5 )O3 as a relaxation agent, so that the A site in the obtained NaNbO3-based perovskite ceramic structure has a high concentration of Bi 3+ , which is conducive to maintaining a higher saturation polarization, thereby obtaining a high energy storage density under medium field strength.
[0078] In step S200, preparing the raw material into powder includes the following steps:
[0079] (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 Preparation of EG3)-xAM powder. Specifically includes the following steps:
[0080] First, a ball milling is performed, the prepared raw materials weighed in the first step are placed in a nylon ball mill, and then anhydrous ethanol and zirconium oxide grinding balls of different diameters are added to obtain a mixture, the speed of the ball mill is controlled to be 350-400 rpm, preferably 380 rpm, and the ball milling time is set to be 20-24 hours. After the ball milling, the mixture is dried at 60-80°C, preferably 80°C, for 6-8 hours. Among them, zirconium oxide is used as a grinding medium, anhydrous ethanol is used as a grinding solvent, the total mass ratio of the prepared raw materials: the total mass of zirconium oxide is 1:1; the diameter range of the zirconium oxide grinding balls is 3-6 mm, and the number ratio of the zirconium oxide grinding balls is controlled to be 6 mm grinding balls: 4-5 mm grinding balls: 3 mm small grinding balls = 1:2:3.
[0081] Next, high-temperature pre-firing is carried out. The mixture that has been ball-milled and dried once is poured into an alumina crucible and calcined at 800-900°C in an air atmosphere in a muffle furnace for 3-5 hours. The heating rate is controlled at 5-8°C / min. After the calcination, the temperature is naturally cooled to room temperature with the furnace so that the ceramic powder can initially form a perovskite structure.
[0082] Then, the secondary ball milling is performed, the high temperature pre-sintered mixture is placed in a nylon ball mill, and then ethanol and zirconium oxide grinding balls of different diameters are added to obtain a mixture, the speed of the ball mill is controlled to be 350-400 rpm, the first ball milling time is set to be 20-24 hours, and after the ball milling, the mixture is dried at 60-80°C for 6-8 hours. Among them, zirconium oxide is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass ratio of the prepared raw materials: the total mass of zirconium oxide is 1:1; the diameter range of the zirconium oxide grinding balls is 3-6 mm, and the number ratio of the zirconium oxide grinding balls is controlled to be 6 mm grinding balls: 4-5 mm grinding balls: 3 mm small grinding balls = 1:2:3.
[0083] In step S300, the processed powder is dried, ground, sieved and the like, and the particle size is greatly reduced. Then, an appropriate amount of binder PVA (polyvinyl alcohol aqueous solution, 3%-5% concentration) is added to grind it, and the ground powder is sieved with 100 mesh.
[0084] In step S500, the ceramic body is first subjected to a binder removal process, wherein the binder removal process is to keep the temperature at 350°C for 1 hour, and then continue to heat the temperature to 500°C for 2 hours, with a heating rate of 5°C / min; the debinded ceramic body is then sintered to obtain the (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramic body is placed in a muffle furnace, the heating rate is controlled at 5-8℃ / min, and the temperature is slowly raised from room temperature to 1150-1200℃, and the sintering time is 3-5h. After sintering, (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramic body is cooled naturally to room temperature in the furnace, and (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramic material. During the debinding process, a heating rate that is too fast will cause pores to form during the debinding process of the ceramic, affecting the density of the ceramic; a heating rate that is too slow will increase the volatilization of volatile elements in the ceramic, causing defects in the ceramic. Therefore, the present invention can obtain dense ceramics with fewer defects by selecting appropriate debinding parameters. During the sintering process, the high temperature during the sintering process also seriously aggravates the Bi 3+ and Na + The volatilization of ions causes defects in ceramics; if the sintering temperature is too low, the density of the ceramics will decrease, seriously affecting the performance of the ceramics (energy storage density, energy storage efficiency). Therefore, the present invention can obtain dense ceramics with fewer defects by selecting appropriate sintering parameters.
[0085] The preparation method of the sodium niobate-based energy storage ceramic material of the present invention will be exemplified below in conjunction with specific embodiments.
[0086] Example 1
[0087] first step,
[0088] Ingredients: Na2CO3, Nb2O5, SrCO3, TiO2, Bi2O3 and MgO are used as raw materials, and the preparation chemical formula is (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 Stoichiometric ratio of O3 system Weigh the above raw materials, where x is 0.10;
[0089] Step 2:
[0090] (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 Preparation of O3 powder. Specifically includes the following steps:
[0091] First, a ball milling is performed, and the prepared raw materials weighed in the first step are placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, and the speed of the ball mill is controlled to be 380 rpm, and the ball milling time is set to be 24 hours. After the ball milling, the mixture is dried at 80°C for 8 hours. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of the zirconia grinding balls is 3-6mm, and the number ratio of the zirconia grinding balls is controlled to be 6mm grinding balls: 4-5mm grinding balls: 3mm small grinding balls = 1:2:3.
[0092] Next, high-temperature pre-sintering is carried out. The mixture that has been ball-milled and dried once is poured into an alumina crucible and calcined at 800°C for 5 hours in an air atmosphere in a muffle furnace. The heating rate is controlled at 8°C / min. After calcination, the mixture is naturally cooled to room temperature along with the furnace.
[0093] Then, the secondary ball milling is performed, the mixture after high temperature pre-sintering is placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, the speed of the ball mill is controlled to be 380 rpm, the secondary ball milling time is set to be 24 hours, and the mixture is dried at 80°C for 8 hours after the ball milling. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass ratio of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of zirconia grinding balls is 3-6mm, and the number ratio of zirconia grinding balls is controlled to be 6mm grinding balls: 4-5mm grinding balls: 3mm small grinding balls = 1:2:3.
[0094] Step 3.
[0095] Granulation: After the processed powder is dried, ground, sieved and other steps, the particle size is greatly reduced, and then an appropriate amount of binder PVA (5% concentration) is added to grind it, and the ground powder is sieved with 100 mesh.
[0096] Step 4.
[0097] Forming tablets: (1-x)0.85NaNbO3-0.15Bi obtained by granulation 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 The O3 powder was placed in a tabletting mold and uniaxially pressed by a powder tabletting machine. The pressure was controlled at 9 MPa and maintained for 60 seconds to obtain (1-x)0.85NaNbO3-0.15Bi with a diameter of 13.5 mm and a thickness of 1.1 mm. 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 O3 ceramic body.
[0098] Step 5.
[0099] Sintering: First, the ceramic body is subjected to a binder removal process, and the binder removal process is to keep the temperature at 350℃ for 1h, and then continue to heat up to 500℃ for 2h, and the heating rate is 5℃ / min; then the obtained (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 The O3 ceramic body was placed in a muffle furnace, and the heating rate was controlled at 8°C / min, and the temperature was slowly raised from room temperature to 1200°C, and kept at this temperature for 3 hours. 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3The O3 ceramic body is naturally cooled to room temperature in the furnace, and the (1-x)0.85NaNbO3-0.15Bi with a thickness of 1.1 mm is obtained. 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 O3 ceramics. Since Na ions and Bi ions are easily volatilized at high temperatures, some oxygen vacancies will be generated, causing defects in the ceramics, resulting in a decrease in saturated polarization intensity and breakdown field strength, and affecting ceramic performance. The present invention greatly reduces the volatilization problem of Na ions and Bi ions, reduces ceramic defects, and ensures the energy storage performance of the ceramics by controlling the sintering temperature, heating rate, and holding time.
[0100] Example 2
[0101] The difference between this embodiment and embodiment 1 is that:
[0102] In the first step, the value of x is 0.04.
[0103] In the second step, (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 Preparation of O3 powder. Specifically includes the following steps:
[0104] First, a ball milling is performed, and the prepared raw materials weighed in the first step are placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, and the speed of the ball mill is controlled to be 350 rpm, and the ball milling time is set to be 24 hours. After the ball milling, the mixture is dried at 60°C for 8 hours. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of the zirconia grinding balls is 3-6mm, and the number ratio of the zirconia grinding balls is controlled to be 6mm grinding balls: 4mm grinding balls: 3mm small grinding balls = 1:2:3.
[0105] Next, high-temperature pre-sintering is carried out. The mixture that has been ball-milled and dried once is poured into an alumina crucible and calcined at 900°C for 3 hours in an air atmosphere in a muffle furnace. The heating rate is controlled at 8°C / min. After calcination, the mixture is naturally cooled to room temperature along with the furnace.
[0106] Then, secondary ball milling is performed, the mixture after high temperature pre-sintering is placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, the speed of the ball mill is controlled to 350 rpm, the secondary ball milling time is set to 24 hours, and the mixture is dried at 60°C for 8 hours after the ball milling. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass ratio of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of zirconia grinding balls is 3-6mm, and the number ratio of zirconia grinding balls is controlled to be 6mm grinding balls: 4mm grinding balls: 3mm small grinding balls = 1:2:3.
[0107] In the third step,
[0108] Granulation: After the processed powder is dried, ground, sieved and other steps, the particle size is greatly reduced, and then an appropriate amount of binder PVA (3% concentration) is added to grind it, and the ground powder is sieved with 100 mesh.
[0109] In the fifth step, sintering: first, the ceramic body is subjected to a debinding treatment, and the debinding process is to keep the temperature at 350°C for 1 hour, and then continue to heat up to 500°C for 2 hours, and the heating rate is 5°C / min; then the obtained (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 The O3 ceramic body was placed in a muffle furnace, and the heating rate was controlled at 5°C / min, and the temperature was slowly raised from room temperature to 1150°C, and kept at this temperature for 5 hours. 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 The O3 ceramic body is naturally cooled to room temperature in the furnace, and the (1-x)0.85NaNbO3-0.15Bi with a thickness of 1.1 mm is obtained. 0.1 Sr 0.85 TiO3-xBiMg 2 / 3 Nb 1 / 3 O3 ceramics.
[0110] Example 3
[0111] The difference between this embodiment and embodiment 1 is that:
[0112] In the first step, the value of x is 0.08.
[0113] In the second step, (1-x)0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3-xBiMg 2 / 3Nb 1 / 3 Preparation of O3 powder. Specifically includes the following steps:
[0114] First, a ball milling is performed, and the prepared raw materials weighed in the first step are placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, and the speed of the ball mill is controlled to be 400 rpm, and the ball milling time is set to be 20 hours. After the ball milling, the mixture is dried at 80°C for 6 hours. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of the zirconia grinding balls is 3-6mm, and the number ratio of the zirconia grinding balls is controlled to be 6mm grinding balls: 5mm grinding balls: 3mm small grinding balls = 1:2:3.
[0115] Next, high-temperature pre-sintering is carried out. The mixture that has been ball-milled and dried once is poured into an alumina crucible and calcined at 800°C for 5 hours in an air atmosphere in a muffle furnace. The heating rate is controlled at 5°C / min. After calcination, the mixture is naturally cooled to room temperature along with the furnace.
[0116] Then, the secondary ball milling is performed, the mixture after high temperature pre-sintering is placed in a nylon ball mill, and then anhydrous ethanol and zirconia grinding balls of different diameters are added to obtain a mixture, the speed of the ball mill is controlled to be 400 rpm, the secondary ball milling time is set to be 20 hours, and the mixture is dried at 80°C for 6 hours after the ball milling. Among them, zirconia is used as a grinding medium, ethanol is used as a grinding solvent, and the total mass ratio of the prepared raw materials: the total mass of zirconia is 1:1; the diameter range of the zirconia grinding balls is 3-6mm, and the number ratio of the zirconia grinding balls is controlled to be 6mm grinding balls: 5mm grinding balls: 3mm small grinding balls = 1:2:3.
[0117] Example 4
[0118] The difference between this embodiment and embodiment 1 is that:
[0119] In the first step, the value of x is 0.12.
[0120] Example 5
[0121] The difference between this embodiment and embodiment 1 is that:
[0122] In the first step, the value of x is 0.16.
[0123] Comparative Example 1
[0124] The difference between this embodiment and embodiment 1 is that:
[0125] In the first step, x takes the value 0.00.
[0126] The prepared sodium niobate-based ceramics with doping amount x=0.00-0.16 were subjected to X-ray diffraction test, and the obtained X-ray diffraction pattern is as follows: Figure 3 As shown, all ceramics have high crystallinity, no impurity phase, and a typical perovskite structure, which indicates that BiMg 2 / 3 Nb 1 / 3 O3 is well integrated into 0.85NaNbO3-0.15Bi 0.1 Sr 0.85 The main lattice of TiO3 forms a solid solution.
[0127] The prepared sodium niobate-based ceramic was plated with gold electrodes by ion sputtering and the hysteresis loop of the material was tested. The unipolar hysteresis loop of the sodium niobate-based ceramic material with a doping amount of x = 0.00 is shown in Figure 4 As shown, it can be seen that in the undoped BiMg 2 / 3 Nb 1 / 3 When O3 is used, the energy loss is large because the residual polarization is large. The breakdown field strength is 177 kV / cm, and the corresponding energy storage density Wrec is 1.86 J / cm 3 , the energy storage efficiency η is 41%. The unipolar hysteresis loop of sodium niobate-based ceramic material with doping amount x = 0.04 is shown in Figure 5 As shown in the figure, the energy loss is greatly reduced compared with that when x = 0.00. This is because BiMg 2 / 3 Nb 1 / 3 O3 doping enhances the relaxivity of the ceramic, resulting in a decrease in the residual polarization, a slender hysteresis loop, and an increase in the breakdown field strength to 269 kV / cm, corresponding to an energy storage density Wrec of 3.99 J / cm 3 , the energy storage efficiency η is 68%. The unipolar hysteresis loop of sodium niobate-based ceramic material with doping amount x = 0.08 is shown in Figure 6 As shown, the energy loss is small, the ceramic relaxation is strong, and a polarized nano-domain is formed inside. The polarized nano-domain can be quickly flipped and recovered after the external electric field is removed, which reduces the residual polarization, makes the hysteresis loop thinner, and increases the breakdown field strength to 337kV / cm. In addition, the appropriate amount of Bi 3+ The high saturation polarization strength of the ceramic (43.6μC / cm 2 ), the corresponding energy storage density Wrec is 6.10 J / cm 3 , the energy storage efficiency η is 81%. The ceramic achieves a high energy storage density (>6J / cm 3 ) (This is attributed to the fact that the ceramic material of the present invention is rich in Bi 3+The hybridization of Bi's 6s orbital and O's 2p orbital allows the ceramic material to maintain a high maximum polarization value, so it only needs a medium electric field strength to obtain a high energy storage density). It has excellent energy storage performance and is expected to be used in wearable devices and microelectronic devices that require high energy storage density under medium field strength (<350kV / cm). The unipolar hysteresis loop of sodium niobate-based ceramic material with a doping amount of x = 0.12 is shown in Figure 7 As shown, the energy loss is small, the relaxivity is strong, the breakdown field strength is 241kV / cm, and the corresponding energy storage density Wrec is 2.93J / cm 3 , the energy storage efficiency η is 81%. The unipolar hysteresis loop of sodium niobate-based ceramic material with doping amount x = 0.16 is shown in Figure 8 As shown, the energy loss is small, the relaxivity is strong, the breakdown field strength is 234kV / cm, and the corresponding energy storage density Wrec is 2.75J / cm 3 , the energy storage efficiency η is 87%. Figures 4 to 8 The different colors in the figure correspond to the hysteresis loops of the ceramic under different electric field strengths. Figures 4 to 8 It can be seen that with the increase of doping amount, the hysteresis loop becomes more and more slender, which is a characteristic of enhanced relaxivity.
[0128] Compare the energy storage density and energy storage efficiency of sodium niobate-based ceramics with x = 0.00 to 0.16, such as Fig. 9 As shown in the figure, it can be found that the energy storage efficiency η increases with the increase of doping amount x. This is because BiMg 2 / 3 Nb 1 / 3 The increase of O3 doping can enhance the relaxation of ceramics, make the hysteresis loop gradually thinner, and reduce energy loss gradually. The energy storage density Wrec increases first and then decreases with the increase of doping amount x. This may be because the high doping amount of BiMg 2 / 3 Nb 1 / 3 During the sintering process, O3 creates some oxygen vacancies or other defects inside the ceramic, resulting in a decrease in the breakdown field strength.
[0129] Example 6
[0130] The difference between this embodiment and embodiment 1 is that:
[0131] In the first step, the ingredients are: Na2CO3, Nb2O5, SrCO3, TiO2, Bi2O3, MgO and HfO2 as raw materials, according to the preparation chemical formula (1-x)(0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3)-xBiMg 0.5 Hf 0.5 The stoichiometric ratio of the O3 system is as follows: the above raw materials are weighed, wherein the value of x is 0.10.
[0132] Example 7
[0133] The difference between this embodiment and embodiment 1 is that:
[0134] In the first step, the ingredients are: Na2CO3, Nb2O5, SrCO3, TiO2, Bi2O3, MgO and ZrO2 as raw materials, according to the preparation chemical formula (1-x)(0.85NaNbO3-0.15Bi 0.1 Sr 0.85 TiO3)-xBiMg 0.5 Zr 0.5 The stoichiometric ratio of the O3 system is as follows: the above raw materials are weighed, wherein the value of x is 0.10.
[0135] According to one aspect of the present invention, there is provided an application of a sodium niobate-based energy storage ceramic material in a device operating under a medium field strength, wherein the sodium niobate-based energy storage ceramic material is the aforementioned sodium niobate-based energy storage ceramic material, or is a sodium niobate-based energy storage ceramic material prepared by the aforementioned method for preparing a sodium niobate-based energy storage ceramic material. These devices are, for example, wearable devices or microelectronic devices, thereby enabling the obtained device to still have a high energy storage density under a medium field strength.
[0136] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. Sodium niobate-based energy storage ceramic material, characterized in that: The general formula of the material is: (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM: A 0.1 D 0.85 EG3 is the general formula of the linear dielectric solid-dissolved in NaNbO3; AM is the general formula of a relaxation agent capable of improving the relaxation characteristics of the material; Wherein, A is a Bi element; the value range of x is 0<x≤0.16; M is the general formula H 2 / 3 J 1 / 3 G3 or general formula H 0.5 L 0.5 G3; wherein H is Mg element, J is Nb element, G is O element, and L is Hf element; D is Sr element; E is Ti element.
2. The sodium niobate-based energy storage ceramic material according to claim 1, characterized in that: The relaxant is a relaxor ferroelectric.
3. The sodium niobate-based energy storage ceramic material according to any one of claims 1 to 2, characterized in that: The value of x is 0.04, 0.08, 0.12 or 0.
16.
4. The method for preparing the sodium niobate-based energy storage ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S10: NaNbO3 is used as the first matrix, and the solid solution formula in the first matrix is A 0.1 D 0.85 EG3 is a linear dielectric, and the general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 Solid solution of EG3; S20: The general formula is 0.85NaNbO3-0.15A 0.1 D 0.85 The solid solution of EG3 is doped with a relaxant capable of improving the relaxation characteristics of the sodium niobate-based energy storage ceramic material, wherein the general formula of the relaxant is AM, and the general formula is (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM sodium niobate-based energy storage ceramic materials; Wherein, A is Bi element; The value range of x is 0<x≤0.16; The general formula is (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 The sodium niobate-based energy storage ceramic material of EG3)-xAM is obtained by sintering. During the sintering process, the temperature is increased from 350°C to 500°C at a heating rate of 5°C / min, and the temperature is kept at 500°C for 2h; and / or The temperature rises from room temperature to 1150~1200℃ at a heating rate of 5~8℃ / min, and is kept at 1150~1200℃ for 3~5h.
5. The method for preparing the sodium niobate-based energy storage ceramic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S100: According to the general formula (1-x) (0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM weigh the raw materials, M is the general formula H 2 / 3 J 1 / 3 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, or M is a general formula H 0.5 L 0.5 G3, raw materials include Na2CG3, Nb2G5, DCG3, EG2, A2G3, HG, LG2; S200: preparing the raw material into powder; S300: granulating the prepared powder; S400: forming and tableting the granulated raw materials to form a ceramic embryo; S500: Sintering the ceramic body to obtain a general formula of (1-x)(0.85NaNbO3-0.15A 0.1 D 0.85 EG3)-xAM ceramics; wherein A is a Bi element; and the value range of x is 0<x≤0.16; In step S500, during the sintering process, the temperature is increased from 350°C to 500°C at a rate of 5°C / min, and maintained at 500°C for 2 hours; and / or The temperature rises from room temperature to 1150~1200℃ at a heating rate of 5~8℃ / min, and is kept at 1150~1200℃ for 3~5h.
6. The method for preparing the sodium niobate-based energy storage ceramic material according to claim 5, characterized in that: D is a Sr element, E is a Ti element, G is an O element, H is a Mg element, J is a Nb element, and L is a Hf element.
7. Application of sodium niobate-based energy storage ceramic materials in equipment working under field strength, characterized in that: The sodium niobate-based energy storage ceramic material is the sodium niobate-based energy storage ceramic material according to any one of claims 1 to 3, or is the sodium niobate-based energy storage ceramic material prepared by the preparation method of the sodium niobate-based energy storage ceramic material according to any one of claims 4 to 6.
Citation Information
Patent Citations
Lanthanum-doped high-energy-storage sodium niobate-based ceramic as well as preparation method and application thereof
CN117658633A